2018
DOI: 10.1186/s12943-018-0882-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of YAP/TAZ activity in cancer metabolic reprogramming

Abstract: In contrast to normal cells, which use the aerobic oxidation of glucose as their main energy production method, cancer cells prefer to use anaerobic glycolysis to maintain their growth and survival, even under normoxic conditions. Such tumor cell metabolic reprogramming is regulated by factors such as hypoxia and the tumor microenvironment. In addition, dysregulation of certain signaling pathways also contributes to cancer metabolic reprogramming. Among them, the Hippo signaling pathway is a highly conserved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 81 publications
3
110
0
Order By: Relevance
“…Many factors, particularly the tumor microenvironment and hypoxia, can regulate metabolic reprogramming to promote the malignant biological properties of tumors . Therefore, the differentially expressed genes (DEGs) in CCA were selected via TCGA database, and we confirmed that the most important DEGs were related to glucose homeostasis and gluconeogenesis by functional enrichment analysis (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Many factors, particularly the tumor microenvironment and hypoxia, can regulate metabolic reprogramming to promote the malignant biological properties of tumors . Therefore, the differentially expressed genes (DEGs) in CCA were selected via TCGA database, and we confirmed that the most important DEGs were related to glucose homeostasis and gluconeogenesis by functional enrichment analysis (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent studies showed that YAP contribute to cancer metabolic reprogramming [21,24], including glycolysis. As studies reported, the activation of YAP can promote glucose uptake and the rate of glycolysis in tumor cells [25][26][27]. However, few studies have reported on the relationship between the two roles of YAP.…”
Section: Introductionmentioning
confidence: 99%
“…Active endocytosis not only regulates PM SA in cells, but is also essential for controlling the surface distribution of a wide-range of membrane proteins including surface receptors and transporters (Antonescu et al, 2014;Bokel and Brand, 2014;Weinberg and Puthenveedu, 2018). Recent studies have suggested that surface expression of glucose transporters and the levels of cytoplasmic glucose can control YAP1 localization and activity (Santinon et al, 2015;Zhang et al, 2018). Therefore, one possibility is that increased CME upon cell fusion changes the distribution of glucose transporters leading to YAP1 nuclear exclusion.…”
Section: Increased Cme Upon Cell Fusion Results In Transient Glucose mentioning
confidence: 99%